The Twenty Attributes of God in ‘Aqidatul ‘Awam and Ahmad Sambas’ Manuscript: A Comparative Analysis - Muafi, Ahmad; Mahrus, Erwin (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to make a comparison between the concept of the twenty-nature of Allah SWT contained in the Book of ‘Aqidatul ‘Awam by Sayyid Ahmad Marzuqi with the concept contained in the Book of Quotations of Ahmad Sambas Mufti Kutai, and analyze its relevance to the development of modern monotheistic education. Through the qualitative Library Research literature research method, it was found that both literatures present the nature of twenty as the foundation of the Ahlussunnah wal Jama'ah faith, but with a different approach. While the Book of Quotations of Ahmad Sambas divides these qualities into the groups of Salbiyah, Ma'ani, and Ma'nawiyah, 'Aqidatul 'Awam is written in the form of a concise nadzam. It also gives a stern warning against the erroneous interpretation that equates beings with the Dzat Allah of the infidel zindiq. In monotheistic education, this comparison has strategic value because it offers a learning model that combines the ‘Aqidatul ‘Awam memorization method with the contextual and analytical approach of Ahmad Sambas Mufti of Kutai. The results of this study emphasize that the study of the nature of the twenty is very important in shaping Muslims who have spiritual strength, moral integrity, and a strong monotheistic consciousness in the midst of the challenges faced by modern society.